New York and the politics of central banks, 1781 to the Federal Reserve Act - Jon R. Moen; Ellis W. Tallman (Federal Reserve Bank of Atlanta, 2003)
The paper provides a brief history of central banking institutions in the United States. Specifically, the authors highlight the role of New York banking interests in the legislations affecting the creation or expiration of central banking institutions. In our previous research we have detected that New York City banking entities usually exert substantial influence on legislation, greater than their large proportion of United States' banking resources. The authors describe how this influence affected the success or failure of central banking movements in the United States, and the authors use this evidence to support their arguments regarding the influence of New York City bankers on the legislative efforts that culminated in the creation of the Federal Reserve System. The paper argues that successful central banking movements in the United States owed much to the influence of New York City banking interests.
Keywords: 330